Perencanaan Pembukuan Sederhana Bagi UMKM Sebagai Pemenuhan Persyaratan UMKM yang Bankable - Risna Cahya Wijayanti; Dwiyani Sudaryanti; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to find out how to improve the knowledge and skills of MSME actors in making simple bookkeeping and to find out how to prepare bankable simple bookkeeping for MSMEs. This research is planned to start from December 2021 to May 2022, taking place in the village of Sambik Bangkol and the village of Rempek, North Lombok Regency. Methods that support this research process are interviews, observation, and documentation. The results of this study found no obstacles in the research process and the increasing ability of MSME actors in making simple bankable bookkeeping.Keywords: Simple bookkeeping, MSME, bankable